Patterns of Fracture Site and Management of Maxillofacial Trauma Cases in The Department of Trauma and Acute Care Surgery in Sanglah General Hospital - Wiargitha, I Ketut; Wiradana, AAGA Anom Arie (JBN (Jurnal Bedah Nasional), 2019)
Aim: To know the patterns of fracture site and management of maxillofacial cases in the Department of Trauma and Acute Care Surgery in Sanglah General Hospital Denpasar Bali. Methods: this is a retrospective study, based on medical record were concluded, samples taken in Sanglah General Hospital from January 2012 to December 2018. All of maxillofacial trauma medical records were taken. The data of age, gender, patterns of fractures site and management were taken and described. Results: There were total of 257 cases of maxillofacial trauma managed in the Department of Trauma and Acute Care Surgery in Sanglah General Hospital. Two-hundred and forty-one medical records of maxillofacial trauma were included in this study. About 16 medical records were excluded due to incomplete medical records and could not be contacted. Mostly cases found in male, aged 18-40 years old. The site of fractures majorly located in the mandible (60.12%). About 48% fractures were identified at symphysis or parasymphysis of mandible, followed by the body and angular of mandible. Open reduction and internal fixation (ORIF) were the gold standard of the treatment (83,73%) followed by Archbarr (16,27%). Conclusion: The most common site of maxillofacial fracture was mandible, specifically at symphysis or parasymphysis part. ORIF miniplate, together with Archbarr and interdental wiring fixation were the most common modality of management.